Asymmetric Decentralization in a Unitary State: Lessons from Pattani, Thailand - Triwahyuningsih, Triwahyuningsih; Islahuddin; Putranti , Deslaely (Journal of Human Rights, Culture and Legal System, 2025)
A unitary state centralizes supreme authority within the national government; however, accommodating regional diversity without undermining national unity remains a persistent constitutional challenge. Indonesia’s Daerah Istimewa Yogyakarta and Thailand’s Pattani region illustrate contrasting approaches to the management of asymmetric decentralization within unitary state frameworks. This study compares the constitutional design of asymmetric decentralization in Yogyakarta and Pattani and examines how each state applies the unitary principle in responding to autonomy claims grounded in local identity. The research employs a comparative qualitative method through normative analysis of constitutional provisions and statutory regulations, supported by interviews with relevant stakeholders. The findings demonstrate, first, that the Thai constitutional and statutory framework does not expressly recognize asymmetric decentralization for Pattani and that the central government grants it no special governmental authority distinct from other provinces. Differentiation is confined to religious, linguistic, and educational regulation. Second, the Indonesian constitutional system explicitly grants Daerah Istimewa Yogyakarta a special legal status that confers extensive autonomous authority based on historical legitimacy and cultural identity. Third, Thailand applies the unitary state principle through a rigid and centralized governance model, whereas Indonesia operationalizes it through an approach in managing diversity.